The Role of Women in Farming Activities and the Coffee Supply Chain in Cigalontang District, Tasikmalaya Regency - Dwi Apriyani; Eri Cahrial; Betty Rofatin; Rizki Risanto Bahar (Universitas Muhammadiyah Palembang, 2024)
Gender involvement in agricultural cultivation cannot be avoided, even though it has the risk of leading to inequality and even injustice. Few ordinary people understand the importance of gender equality and dynamics in the agricultural sector. The research aims to describe the characteristics of coffee farmers in Cigalontang District and map the allocation of women's work time in social, economic and domestic activities in coffee farming. The research method used is qualitative descriptive analysis and mathematical formulas for calculating women's work time in the economic, social and domestic fields, according to the Harvard framework. The research results show that the majority of coffee farmers are over 50 years old with the majority's education level being elementary school graduates. The land ownership status is mostly sharecroppers with an average of 0.18 ha to 2.6 ha of total cultivated land. Meanwhile, most farmers have 2.5 to 8.4 years of cultivation experience. As for the time spent by women coffee farmers as housewives, the most dominant time is allocated to domestic activities. Meanwhile, coffee farmers who work as traders and service providers spend most of their time on economic activities. Women coffee farmers with trading and service professions allocate less time for social activities than women coffee farmers who work as housewives.